شرح الشبراخيتي على مختصر خليل للعلامة إبراهيم بن مرعى بن عطية الشبراخيتي(ت1106ه) - سليماني, حورية (University of Eloued-جامعة الوادي, 2022)
" فهذه المذكرة الموسومة بـ: ""شرح ‌الشَّبْرَاخِيتِيِّ على مختصر خليل للعلامة إبراهيم بن مرعي بن عطية ‌الشَّبْرَاخِيتِيِّ (ت: 1106ه) باب الوكالة -دراسة وتحقيق-"" تناولت فيها تحقيق باب الوكالة من شرح الإمام ‌الشَّبْرَاخِيتِيِّ المسمّى: ""شرح ‌الشَّبْرَاخِيتِيِّ على مختصر خليل""، وذلك من خلال الإجابة على الإشكال الرئيس: ماهي القيمة العلمية لشرح الإمام ‌الشَّبْرَاخِيتِيِّ على مختصر خليل؟. ويتفرع عنه عدّة إشكالات فرعية، من أهمها: هل النص خال من التشويه والنقص والزيادة؟ وهل نسبة النص إلى مؤلِّفه صحيحة؟ وهل للإمام ‌الشَّبْرَاخِيتِيِّ ترجيحات واختيارات فقهية خالف بها من قبله؟ أم هو مجرّد ناقل لكلام العلماء؟ وهل للإمام ‌الشَّبْرَاخِيتِيِّ تعقبات واستدراكات على الإمام خليل؟ وهل له عناية بضبط متن المختصر للإمام خليل؟. وللإجابة على هذه الإشكالات قمنا بتقسيم هذه الدراسة إلى قسمين؛ القسم الأول للدراسة، وقسمته إلى ثلاثة مباحث؛ المبحث الأول يتضمن التعريف بالإمام ‌الشَّبْرَاخِيتِيِّ، والثاني للتعريف بشرحه، والمبحث الثالث: للتعريف بالنسخ المعتمدة في التحقيق وبيان منهجي فيه، أما القسم الثاني فقد خصصته لتحقيق باب الوكالة من خلال نسخ المخطوطة ومقابلتها. وأهم النتائج التي خلصت إليها من خلال هذا البحث: أن لشرح الإمام ‌الشَّبْرَاخِيتِيِّ على مختصر خليل قيمة علمية كبيرة، تظهر من خلال اختياراته وترجيحاته وتعقباته، وأشرت إلى عدّة توصيات من أهمها: دعوة إدارة قسم الشريعة بمعهدنا المبارك إلى تبني مشروع تحقيق ما تبقى من شرح ‌الشَّبْرَاخِيتِيِّ على مختصر خليل وتوزيعه على طلبة الدكتوراه والماستر. "" This note is entitled: “Explanation of Al-Shabrakhiti on the Mukhtasar Khalil by the scholar Ibrahim bin Marei bin Attia Al-Shabrakhiti (died: 1106 AH) chapter of alwakala - study and realization -”. I dealt with the realization of alwakala chapter from the explanation of Imam Shabrkhiti called: “Sharh al-Shabrakhiti on Mukhtasar Khalil”, by answering the main problem: What is the scientific value of Imam al-Shabrakhiti’s explanation of Mukhtasar Khalil? It has several sub-problems, the most important of which are: Is the text free from distortion, deficiency, and increase? Is the attribution of the text to his author correct? Does Imam al-Shabrakhiti have doctrinal preferences and choices that he disagreed with who before him? Or is he just a transmitter of the utterance of the scholars? Does Imam al-Shabrakhiti have rectifications on Imam Khalil? Does he care about tuning the text of Imam Khalil’s Mukhtasar? To answer these problems, we divided this study into two parts. The first part of the study, which was divided into three sections; the first includes the definition of Imam Al-Shabrakhiti, the second is to define his explanation, and the third section: to define the copies approved in the realization and indicating my method in it. The second part was devoted to the realization of alwakala chapter through the copies of the manuscript and comparing them. The most important findings that I concluded through this research: that Imam Shabrakhiti’s explanation on the Mukhtasar Khalil has great scientific value, which appears through his choices, preferences, and rectifications, and I referred to several recommendations, the most important of which are: Inviting the administration of the Sharia Department at our blessed institute to adopt the project of realizing the rest of the Shabrakhiti explanation on Mukhtasar Khalil and distributing it to doctoral and master students "
مذكرة ماستر
Keywords: " الكلمات المفتاحية: شرح- ‌الشَّبْرَاخِيتِيِّ –مختصر خليل-باب الوكالة-دراسة وتحقيق"; key words: Explanation - Al-Shabrakhiti - Mukhtasar Khalil -chapter of alwakala - study and realization.